Effect of short-term exercise with different programs on prevention of sarcopenia in postmenopausal women: A Quasi-Randomized Controlled Trial - Neng Pan; Katarzyna Krasowska; Ossowski Zbigniew (PLoS ONE, 2025)
Background Physical exercise is an effective measure to prevent sarcopenia. However, the effects of Nordic walking based on high-intensity interval training (HIIT NW) and conventional strength training (ST) on the parameters related to sarcopenia in postmenopausal women remain unclear. Therefore, this study aims to evaluate the effects of 12-week HIIT NW and ST on body composition and physical function performance in postmenopausal women. Method The participants were 71 women aged between 60 and 79 years old without sarcopenia. Participants were randomly assigned to the HIIT NW group (12-week Nordic walking training, 3 × /week), the ST group (12-week strength training, 3 × /week), and the control group. The body composition was determined by using Otupole InBody 720. Test the hand grip strength with a digital hand force gauge. The strength of the extensor and flexor muscles of the knee joint was measured using Biodex System 4 Pro™. This study also employed common methods for measuring functional performance and conducted two measurements of blood creatinine and creatine kinase. Result Compared with the control group, significant improvements were observed in parameters such as Time Up and Go (TUG) and knee joint flexor strength (KFS) in both the HIIT NW group and the ST group. In the ST group alone, significant enhancements were noted in parameters including walking speed (GS) and hand strength on the left side (HS-L). Following the intervention, the HIIT NW group exhibited a marked increase in limb lean mass, which led to a significant rise in the skeletal muscle index (SMI) (p < 0.001). However, the body fat mass (BFM) and body mass index (BMI) decreased significantly in the ST group (p < 0.001 and p = 0.005, respectively). No significant changes were observed in the control group. Conclusion Both HIIT NW and ST interventions can effectively prevent sarcopenia in postmenopausal women. The former focuses on improving lower limb strength, while the latter focuses on improving upper limb strength. In the short term, the HIIT NW intervention model is more beneficial for postmenopausal women with normal weight, while the conventional ST intervention model is more conducive to the overweight population.